Realities and myths of the Teresken Syndrome - An evaluation of the exploitation of dwarf shrub resources in the Eastern Pamirs of Tajikistan - Kraudzun, Tobias; Vanselow, Kim; Samimi, Cyrus (Journal of Environmental Management, 2014)
We argue that the term 'Teresken Syndrome', which was introduced after the emergency replacement of Soviet coal supplies by dwarf shrubs in the 1990s, is not appropriate anymore to describe the current use of natural resources in the Eastern Pamirs. However, under the current economic circumstances the nexus remains that the Pamir people are caught in the dilemma of using dwarf shrubs as energy and as forage resource. However, the observed negotiation practices concerning competitive use between dwarf shrub extractors and herders could be developed into community-based management schemes of this common pool resource. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Natural resources; Thermal energy; Firewood extraction; Land degradation; Post-Soviet transformation; Pastoralism